2020
DOI: 10.3390/nu12123860
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Approaches for the Management of Nonalcoholic Fatty Liver Disease: An Evidence-Based Review

Abstract: Nonalcoholic fatty liver disease (NAFLD) is on the rise worldwide representing a public health issue. Its coexistence with obesity and other metabolic alterations is highly frequent. Therefore, current therapy interventions for NAFLD are mainly focused on progressive weight loss through modulation of overall calorie intake with or without specific macronutrient adjustments. Furthermore, other relevant nutritional interventions are built on food selection and time-restricted eating. Since every strategy might b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 94 publications
1
38
0
1
Order By: Relevance
“…Relevantly, in our study, we observed an 8.1% reduction of body weight and a significantly lower body weight gain in the animals supplemented with CMA at Dose II when compared to their HFD counterparts, which strongly suggest a strong potential of our multi-ingredient treatment to tackle NAFLD also through weight loss. This is also in agreement with our hypothesis to use multi-ingredient-based supplements that act against complementary targets, such as CMA, as potential strategies to effectively tackle this multifactorial disease, since different studies have claimed that better outcomes against NAFLD are obtained when treatments are performed under a multifaceted approach [7]. Three mechanisms responsible for the body weight loss produced by the supplementation of bioactive compounds are the inhibition of food intake, the enhancement of energy expenditure (EE), and the regulation of lipid metabolism [86].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Relevantly, in our study, we observed an 8.1% reduction of body weight and a significantly lower body weight gain in the animals supplemented with CMA at Dose II when compared to their HFD counterparts, which strongly suggest a strong potential of our multi-ingredient treatment to tackle NAFLD also through weight loss. This is also in agreement with our hypothesis to use multi-ingredient-based supplements that act against complementary targets, such as CMA, as potential strategies to effectively tackle this multifactorial disease, since different studies have claimed that better outcomes against NAFLD are obtained when treatments are performed under a multifaceted approach [7]. Three mechanisms responsible for the body weight loss produced by the supplementation of bioactive compounds are the inhibition of food intake, the enhancement of energy expenditure (EE), and the regulation of lipid metabolism [86].…”
Section: Discussionsupporting
confidence: 90%
“…So far, the most effective strategy to counteract NAFLD is weight loss and the adherence to healthier life style habits, including hypocaloric diets and physical exercise [5][6][7]. However, this long-term strategy fails in most of the subjects because it is extremely difficult to maintain body weight reduction (lost weight is usually gradually regained) and due to the poor adherence to hypocaloric diets, which, in many cases, have a low palatability.…”
Section: Introductionmentioning
confidence: 99%
“…Several different diets have been tested in patients with NAFLD [ 18 , 22 ]. Observational studies and small randomized controlled trials (RCTs) have consistently documented that the Mediterranean diet has favorable effects in patients with NAFLD and, in addition, it is able to reduce liver fat, as well as improve metabolic profile, regardless of weight loss [ 22 , 23 , 24 , 25 ]. For such reasons, at present, the Mediterranean diet is the most recommended dietary pattern in NAFLD patients by most guidelines [ 1 , 2 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in a randomized, parallel-group design trial of 51 obese patients with NAFLD who were randomly assigned to a 12-week single-blinded dietary intervention (i.e., ad libitum isocaloric Mediterranean diet or low-fat diet), Properzi et al documented that hepatic steatosis (evaluated by magnetic resonance spectroscopy) decreased significantly in both groups, with no difference in terms of mean percentage reductions in liver fat content [ 33 ]. Potential molecular mechanisms for the favorable effects of the Mediterranean diet include the presence of polyphenols, carotenoids, oleic acid, polyunsaturated fatty acids (PUFAs), and fiber [ 22 , 24 ]. These components might favorably influence some pathways involving the intestine, adipose tissue, and liver, thereby mediating favorable effects in NAFLD [ 24 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation